The Role of B1 Cells in Systemic Lupus Erythematosus - She, Zhou; Li, Cuifang; Wu, Feifeng; Mao, Jueyi; Xie, Min; Hun, Marady; Abdirahman, Amin Sheikh; Luo, Senlin; Wan, Wuqing; Tian, Jidong; Wen, Chuan (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by multi-systemic and multi-organ involvement, recurrent relapses and remissions, and the presence of large amounts of autoantibodies in the body as the main clinical features. The mechanisms involved in this disease are complex and remain poorly understood; however, they are generally believed to be related to genetic susceptibility factors, external stimulation of the body’s immune dysfunction, and impaired immune regulation. The main immune disorders include the imbalance of T lymphocyte subsets, hyperfunction of B cells, production of large amounts of autoantibodies, and further deposition of immune complexes, which result in tissue damage. Among these, B cells play a major role as antibody-derived cells and have been studied extensively. Yet, B1 cell mechanisms remain unclear. In this review, we focus on the mechanism of B1 cells in SLE to provide new directions to explore the pathogenesis and treatment modalities of SLE.